Upaya Satuan Binmas Melalui Kegiatan Penyuluhan Dalam Mencegahan Pencurian Pada Kendaraan Jenis Roda Dua - Ivan Bagus Pratama (Police Studies Review, 2019)
The focus of this thesis is the description of the Binmas Unit's Efforts Through Counseling Activities in Preventing Theft on RodaTua-type Vehicles in the Tasikmalaya Police Region. The problems raised in this thesis, namely: What is the description of the crime of theft of two-wheeled motor vehicles in the area of ​​the Tasikmalaya Polres, How are the efforts made by the Binmas Unit in overcoming obstacles in preventing the theft of two-wheeled motor vehicles in the Tasikmalaya district police jurisdiction, what factors are affect the activities of the Binmas Unit in preventing the theft of two-wheeled motor vehicles in the law area of ​​the Tasikmalaya Police Station. This study uses a qualitative approach with field research methods. Theories used in this research are management theory and communication theory, while the concept used is the binmas unit concept, the concept of criminal acts and the concept of theft. Data analysis techniques using data reduction, data presentation and conclusion drawing. As for the place of research conducted by the author in the area of ​​law police in Tasikmalaya. The conclusions in this research are: The counseling activities carried out by the Tasikmalaya Police Bin Bin Saturn are outlined in the daily plan, weekly plan and monthly plan. The targets of counseling in the ritual are religious leaders, community leaders, NGOs, mass organizations, and the community in the Tasikmalaya district police jurisdiction. Obstacles in preventing theft on two-wheeled vehicles in the Tasikmalaya Police Region, namely: human resources, budget and infrastructure. Efforts that can be carried out by the Binmas Unit are as follows: Conduct training for members of the Tasikmalaya Regional Police Binmas, adding facilities and infrastructure existing, Making addicts of Kambtibmas by placing banners in strategic places (prone to theft, mosques, crowded places, etc.)